THE ABSOLUTE COMPETENCE OF THE JURISDICTION OF THE ADMINISTRATIVE COURT IN A DISPUTE WHOSE OBJECT IS A FICTIVE-POSITIVE KTUN - Francisca Romana Harjiyatni (Mimbar Hukum, 2017)
Abstract Based on the Law on Administrative Court, the Administrative Court has the competence to examine and decide upon a dispute whose object is a fictive- negative decision (KTUN). After the enactment of the Law No. 30 of 2014 on Government Administration, the Administrative Court has the competence to examine and decide a dispute whose object is a fictive positive KTUN. The provision of the positive decision in the Law No. 30 of 2014 provides fairer legal protection to both procedural justice and substantive justice. However, the force power of the court to execute decision remains low. Consequently, a fair legal protection to the dispute of positive KTUN per the Law No. 30 of 2014 is not optimal.